KOORDINASI DIREKTORAT JENDERAL PAJAK DENGAN PEMERINTAH KABUPATEN SERDANG BEDAGAI DALAM OPTIMALISASI PENERIMAAN PAJAK PUSAT - Sinaga, Womsiter; Sumaryadi, I Nyoman; Simangunsong, Fernandes; Sinurat, Marja (Prodi Ilmu Pemerintahan FISIP Universitas Komputer Indonesia, 2022)
Taxes are needed to finance government operations, for central and local governments. DGT's coordination with the Serdang Bedagai Regency Local Government is crucial for optimizing central tax. This study aims to analyze the coordination between the Directorate General of Taxes and the Local Government of Serdang Bedagai Regency. This study utilizes descriptive qualitative approach. This study found that the two parties’ coordination isn’t maximized, there’s no Regent Regulation optimizing central tax revenues. It’s not formally made in a Cooperation Agreement (PKS) for synchronizing activities– furthermore unsupported by an information system. The local government and DGT’s technology are unintegrated. The intensification and extensification activities are lacking. Supervision of the Treasurer is implemented ineffectively. Data informations’ exchange between the Local Government and the DGT has been inadequate.